Apakah Karakteristik Direksi Mempengaruhi Kinerja Keuangan BUMN? - Magdalena, Theresia; Setiawan, Doddy; Aryani, Y Anni; Widarjo, Wahyu (Universitas Swadaya Gunung Jati, 2024)
SOE companies have implemented regulations PER-08 / MBU / 08/2020 related to long-term plans, one of which is improving governance in determining the board of directors. This study aims to help optimize the influence of the characteristics of the board of directors on financial performance as measured by return on assets, so that it can make a board of directors more effective in controlling companies that are under government supervision. Seeing the diversity of research results, this study specifies the non-financial sector. The data used are secondary data obtained from each company website included in the Ministry of BUMN. The population in this study consisted of 56 companies in 2018-2022 with a sample size of 280 observations with unbalanced panel data. Tests were carried out through descriptive statistical tests and multiple linear regression using the EVIEWS 12 statistical tool. As a result of the study, it was found that female directors have a positive significance because they have better accounting practices on financial performance while the educational background of directors and board meetings are not significant. SOE companies can optimize the increase of female directors so that the development of strategies in decision-making effectively impacts the financial performance of the company.